ADHD in women - a review - Agnieszka Brzezińska; Monika Borowiecka; Marlena Zając; Konrad Warchoł; Wiktor Michniak (Kazimierz Wielki University, 2021)
Introduction: Attention-deficit hyperactivity disorder (ADHD) for many years has been thought to occur mainly in the male population. However, recent studies and change in professionals' perception allowed us to understand that there are significant differences between predominant features related to the gender of the affected person, which changes our look at how the condition may exhibit in women.  Current state of knowledge: In this review, we provide a general look at the disorder, its characteristics in the young and adult population, differences in symptoms and finally -  how it may prove difficult to diagnose this condition among women. Several factors that could contribute to development of ADHD were listed in literature, among them genetics, prenatal period, diet and parents' emotional wellbeing. Concerning women, they are considered to internalize their psychological struggles, such as depression and stress more often than men, rendering them more susceptible toward suicidal behaviors and making diagnosis harder. Conclusions: When it comes to diagnosis in women, the main difficulty is that the symptoms are presented in a different way compared to men suffering from the same disorder. Because of those reasons, it's harder to make a proper diagnosis. Therefore, further studies, taking account of affected one's gender needs to be conducted, while medical professionals have to be more cautious.